2008
DOI: 10.1002/14651858.cd007031
|View full text |Cite
|
Sign up to set email alerts
|

Ciclesonide versus other inhaled steroids for chronic asthma in children and adults

Abstract: The results of this review give some support to ciclesonide as an equivalent therapy to other ICS at similar nominal doses. The studies assessed low doses of steroids, in patients whose asthma required treatment with low doses of steroids. At half the dose of FP and BDP/BUD, the effects of ciclesonide were more inconsistent The effect on candidiasis may be of importance to people who find this to be problematic. The role of ciclesonide in the management of asthma requires further study, especially in paediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
0
19
0
3
Order By: Relevance
“…In other trials, ciclesonide has been shown to be equivalent to fluticasone in increasing FEV1 [33]. The smaller effect of ciclesonide on small airway parameters, such as FEF25-75% and alveolar eNO, compared with fluticasone is even more surprising.…”
Section: Discussionmentioning
confidence: 92%
“…In other trials, ciclesonide has been shown to be equivalent to fluticasone in increasing FEV1 [33]. The smaller effect of ciclesonide on small airway parameters, such as FEF25-75% and alveolar eNO, compared with fluticasone is even more surprising.…”
Section: Discussionmentioning
confidence: 92%
“…Guidelines recommend that fluticasone and ciclesonide be prescribed at similar nominal doses123615 based on equipotence in formal testing in randomized trials. Despite these recommendations, we found that in practice, ciclesonide was prescribed at lower doses than fluticasone and that fluticasone was typically prescribed at higher than recommended doses, corroborating findings from prior studies in the Netherlands, as well as New Zealand, the UK, and the USA 21223940.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials to date, ciclesonide showed similar efficacy as compared with fine-particle ICSs, such as fluticasone and budesonide (MMAD ~3 µm) at similar nominal doses for patients with persistent asthma 101516. However, these trials were generally 8-12 weeks in duration and focused on short-term improvement of lung function outcomes, thus they were unable to assess longer term fluctuations in asthma control and events, such as exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, perhaps as a consequence of the inactive inhaled compound, ciclesonide has a different adverse effect profile. Most markedly, a reduction in oral candidiasis of 75% when compared with FP has been demonstrated [52]. Second, ciclesonide is a small-particle ICS, thus reaching more distal airways of smaller caliber than ICS with larger particles.…”
Section: Market Reviewmentioning
confidence: 98%
“…A systematic review and meta-analysis of the clinical efficacy of ciclesonide in asthma was published in 2008. In that article, some support was found that ciclesonide is likely not to be inferior to other ICS, but more studies were warranted at that point [52]. More recently, in 2014, a fairly large step-down study of asthmatics comparing ciclesonide q.d.…”
Section: Market Reviewmentioning
confidence: 99%